Effect of postmortem storage on shear force value and calpain/calpastatin activity in longissimus dorsi muscle of rusa deer (cervus timorensis) - Orapin Jantasaeng; Kanya Jirajaroenrat; Kunya Tuntivisoottikul (My University, 2018)
The objective of this study was to determine the effects of aging period on shear force values and activities of calpain/calpastatin enzymes of the longissimus dorsi (LD) muscle from rusa deer (Cervus timorensis) . The shear force values were measured with instron materials testing machine. Results showed that postmortem storage influenced meat tenderness with a highly significant reduction of shear force value from 9.01±0.83 kg/cm 2 at day 1 to 4.34±0.10 kg/cm 2 at day 21 (P<0.01). Determination of the enzyme activities indicated that the μ-calpain activity decreased significantly from 1.50±0.42 to 0.19±0.28 units/g of meat (P<0.01), whereas m-calpain activity (22.88±9.64 to 16.95±8.34 units/g of meat) and calpastatin activity (9.93±2.37 to 6.82±2.96 units/g of meat) slightly decreased (P>0.05). Shear force values were significant correlated with higher levels of μ-calpain (r=0.915) and m-calpain (r=0.758), respectively. However, the values were not significant related to the calpastatin activity (r=0.462). Therefore, this study confirmed that in the case of rusa deer, μ-calpain is a key factor controlling postmortem meat tenderness compared to m-calpain and calpastatin. The results suggested that storage of the rusa deer meat for 7 days is enough to achieve aging of the LD muscle, which may help to reduce the cost of meat production.
Keywords: Calpastatin; Meat tenderness; Longissimus dorsi; Longissimus muscle; Cervus; Longissimus; Meat and Animal Product Quality